2020
DOI: 10.1155/2020/7829842
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng Inhibits Tau Aggregation and Promotes Tau Dissociation In Vitro

Abstract: Tau, a microtubule-associated protein expressed in mature neurons, interacts with tubulin to promote the assembly and stabilization of microtubules. However, abnormally hyperphosphorylated tau dissociates from microtubules and self-aggregates. Tau aggregates, including paired helical filaments and neurofibrillary tangles, promote neuronal dysfunction and death and are the defining neuropathological feature of tauopathies. Therefore, suppressing tau aggregation or stimulating the dissociation of tau agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Mitochondrial function can also be regulated by melatonin [ 396 ], methylene blue [ 397 ], carotenoids [ 398 ], red gingseng [ 399 ], and oxaloacetate [ 400 ]. Most of these supplements have multiple effects, e.g., inhibition of tau aggregation may be involved in the effects of methylene blue [ 337 , 401 ], red gingseng [ 402 ], crocin [ 403 ], cinnamaldehyde and epicatechin [ 404 ], purpurin [ 405 ], and folate [ 406 ], and inhibition of Aβ toxicity may be involved in the effects of resveratrol [ 407 ], huperzine A (cholinesterase inhibitor and NMDA receptor antagonist) [ 408 , 409 ] and carvacrol (anti-acetylcholinesterase, antioxidant, and neuroprotective properties) [ 410 , 411 ].…”
Section: Alzheimer’s Drugsmentioning
confidence: 99%
“…Mitochondrial function can also be regulated by melatonin [ 396 ], methylene blue [ 397 ], carotenoids [ 398 ], red gingseng [ 399 ], and oxaloacetate [ 400 ]. Most of these supplements have multiple effects, e.g., inhibition of tau aggregation may be involved in the effects of methylene blue [ 337 , 401 ], red gingseng [ 402 ], crocin [ 403 ], cinnamaldehyde and epicatechin [ 404 ], purpurin [ 405 ], and folate [ 406 ], and inhibition of Aβ toxicity may be involved in the effects of resveratrol [ 407 ], huperzine A (cholinesterase inhibitor and NMDA receptor antagonist) [ 408 , 409 ] and carvacrol (anti-acetylcholinesterase, antioxidant, and neuroprotective properties) [ 410 , 411 ].…”
Section: Alzheimer’s Drugsmentioning
confidence: 99%
“…J-147, an oral curcumin derivative, has been demonstrated to easily cross BBB and enhance memory in aged AD mice [118] . In addition, purpurin [119] , ginseng [120] , and many other natural compounds are also being investigated, which will offer great potential for the treatment of AD.…”
Section: Preventing Tau Aggregationmentioning
confidence: 99%
“…Another in vitro study has revealed that α-cyperone from rhizomes of Cyperus rotundus (Cyperaceae) exerts a significant effect on reducing the rate of tubulin polymerization and the concentration of polymerized tubulin, which may represent a beneficial neuroprotective strategy for AD [ 155 ]. Other well-known examples of natural products capable of inhibiting tau protein aggregation are curcumin, which inhibits amyloidogenic protein aggregation including Aβ and tau [ 156 ], resveratrol, which inhibits the aggregation of the repeat domain of tau along with many other neuroprotective mechanisms [ 157 ], purpurin, which inhibits tau fibrillization and breaks down the pre-formed fibrils [ 158 ], folic acid, which inhibits tau aggregation via stabilizing its native state [ 159 ], and the root extract of red ginseng [ 160 ].…”
Section: Neuroprotective Mechanisms Of Natural Products For Admentioning
confidence: 99%